Potential Fermentation of Sweet Potato Pickle (Ipomoea batatas L.) with Lactobacillus plantarum B1765 in the Production of Short Chain Fatty Acids - Insani, Yasinta Rizqi; Wikandari, Prima Retno (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Short-chain fatty acid (SCFA) is the final metabolic product of inulin that can provide various health benefits. In this study, the effect of fermentation duration of sweet potato pickle using Lactobacillus plantarum B1765 starter culture in the production of SCFA was studied, as well as its relationship with total Lactic Acid Bacteria (LAB), pH, and Total Titratable Acid (TTA). Fermentation was carried out with the addition of starter culture as much as 10% (v/v) at 37ºC for 4, 8, 12, 24, and 0 hours which was used as a control. The number of LAB was measured using the Total Plate Count (TPC) method, pH value was measured with a pH meter, TTA was measured using the acid-alkalimetric titration method, and SCFA was measured using an HPLC instrument with 0.1% H3PO4 eluent and 25% acetonitrile. Fermentation duration affects LAB growth, TTA, SCFA, and pH. The results showed that total LAB growth was optimal at 8 hours fermentation time at 2.81×108 CFU/mL, which increased by 2 log cycles from the initial fermentation time of 0 hours. Still, the pH decreased until it reached 3.23 ± 0.20, and TTA increased to 0,56 ± 0.02% until the end of fermentation at 24 hours. SCFA also increased until the end of fermentation at 24 hours, where acetic acid levels showed the highest levels (6.85 ± 0.30 mg/mL), followed by propionic acid (5.04 ± 0.20 mg/mL) and butyric acid (2.14 ± 0.10 mg/mL). Sweet potato pickles fermented with L. plantarum B1765 starter culture have met the SNI 01-3784-1995 standard and have the potential to be developed as a functional food source of SCFA, which has many health benefits.